Parasitological, Molecular, and Epidemiological Investigation of Cryptosporidium Infection Among Cattle and Buffalo Calves From Assiut Governorate, Upper Egypt: Current Status and Zoonotic Implications - Elmahallawy, Ehab Kotb; Sadek, Hesham A.; Aboelsoued, Dina; Aloraini, Maha A.; Alkhaldi, Abdulsalam A. M.; Abdel-Rahman, Salma M.; Bakir, Hanna Y.; Arafa, Mohsen I.; Hassan, Ehssan Ahmed; Elbaz, Elzahara; Hassanen, Eman A. A.; El-Gohary, Fatma A.; et al. (Frontiers in Veterinary Science, 2022)
Details about the epidemiological patterns and real contributions of different reservoir animals in maintaining the transmission cycle of Cryptosporidium spp. in Upper Egypt remain lacking. This study was designed to investigate the occurrence of Cryptosporidium spp. in cattle and buffalo (n = 608) from Upper Egypt. The parasite for the resulting positive samples by fecal examination was molecularly identified using nested polymerase chain reaction (nested PCR) targeting the small subunit rRNA. Moreover, several explanatory variables, including animals’ age, sex, and condition and seasonal variations, were examined to describe the epidemiological pattern of the disease. Interestingly, the fecal examination revealed that 33.55% (204/608) of the animals under study were infected with Cryptosporidium, including 38.27% among cattle and 28.16% among buffalo. The parasite was molecularly identified using nested PCR, and their amplicons were identified in almost all fecal samples using microscopy (202/204). According to age as an individual variable factor, the infection rates of Cryptosporidium spp. in cattle calves with ages of <1 month, 1–3 months, and >3 months were 39.13%, 34.04%, and 54.54%, respectively. Meanwhile, in buffalo calves, the occurrence rates were 28.57%, 27.27%, and 29.41%, respectively. Regarding sex, female cattle calves were more susceptible to Cryptosporidium infection (51.28%) than males (26.19%) (p < 0.05), whereas male buffalo calves had a higher infection rate (32.25%) than females (25%). According to seasonal variations, the infection rates of Cryptosporidium spp. in cattle calves during spring, summer, autumn, and winter were 42.11%, 30.43%, 30%, and 52.63%, respectively. In contrast, lower infection rates of 30%, 21.42%, 23.52%, and 35% were reported in buffalo calves during spring, summer, autumn, and winter, respectively. The rate of infection was 45.16% in diarrheic cattle calves and 15.78% in non-diarrheic ones (p < 0.05). Meanwhile, the infection rate was 33.96% in diarrheic buffalo calves and 11.11% in non-diarrheic ones (p < 0.05). This study reported a higher occurrence of Cryptosporidium infection among the animals under study and revealed that buffalos and cattle can contribute to maintaining the transmission cycle of this zoonotic parasite in Upper Egypt.